Association Between Daily Sample Collection Time and Results of Testosterone Testing in Adult Males. (9th November 2022) - Windham, A K; Brimhall, B; Nguyen, K
Abstract: Introduction/Objective: Serum testosterone levels in men have diurnal fluctuation with levels peaking between 7 AM and 10 AM, reaching an early evening nadir around 7 PM. For evaluation of male hypogonadism, fasting total testosterone levels should be measured in the early morning (8 to 10 AM). Testosterone measurements made beyond peak times may yield misleading results. We aim to investigate specimen collection times and compare with testosterone levels. Methods/Case Report: We examined specimen collection times for testosterone testing (n=3075) for adult males (age >16 years) over a four-year period (July 2016-June 2020). Collection times were grouped into 2-hour intervals and test interpretations were grouped as either "low" or "high/normal". Collection times were categorized as either morning (between 6 AM and 12 PM) or non-peak times (between 12 PM and 6 AM) A chi-square analysis was performed to investigate the possible relationship between low testosterone levels and specimen collection time. Results (if a Case Study enter NA): Approximately two-thirds of testosterone test samples were collected outside the recommended timeframe of 8-10 AM and accounted for 70% of low testosterone levels. The chi-square test showed that there is a significant (p=0.005) overall relationship between specimen collection times and testosterone levels. A correspondence plot of chi-square residuals showed a positive relationship between low testosterone levels collected at non-peak times. Conversely, there was a negative relationship between low testosterone levels collected in the morning. Conclusion: Low testosterone levels measured on specimens collected outside of peak morning hours may be difficult to interpret and may lead to additional unnecessary repeat testing or treatment.